2021
DOI: 10.3389/fphar.2021.590477
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology-Based Strategy for Elucidating the Molecular Basis Forthe Pharmacologic Effects of Licorice (Glycyrrhiza spp.)

Abstract: Licorice (Glycyrrhiza spp.) is used widely in traditional Chinese medicine (TCM) due to its numerous pharmacologic effects. However, the mechanisms of action of the chemical constituents of licorice and their structure–function relationships are not fully understood. To address these points, we analyzed the chemical compounds in licorice listed in the TCM Systems Pharmacology database and TCM Integrated database. Target proteins of the compounds were predicted using Integrative Pharmacology-based Research Plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…Since GA has been reported to have a strong protective function in ANIT‐induced cholestasis (Wu et al, 2018), how about the other main active ingredient in licorice? Liquiritin (LQ) is an important monomer active component in flavonoids of licorice (Chen et al, 2021). However, the study on the effect and mechanism of LQ on cholestatic liver injury is rare.…”
Section: Introductionmentioning
confidence: 99%
“…Since GA has been reported to have a strong protective function in ANIT‐induced cholestasis (Wu et al, 2018), how about the other main active ingredient in licorice? Liquiritin (LQ) is an important monomer active component in flavonoids of licorice (Chen et al, 2021). However, the study on the effect and mechanism of LQ on cholestatic liver injury is rare.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the various phyto-constituents from Glycyrrhiza species, especially G. glabra , comprise more than 20 tri-terpenoids and approximately 300 flavonoids [ 8 , 4 ]. Moreover, the roots of G. glabra (Licorice) have been reported to possess a high content of glycyrrhizin (tri-terpene saponin) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Network pharmacology meets the holistic view of TCM theory, and is an effective strategy to elucidate the potential active compounds and action mechanisms of TCM (Zhu et al, 2019). Chen et al employed network pharmacology to elucidate the chemical basis and molecular mechanisms for the pharmacological effects of licorice, and carried out experimental verification (Chen, Li, Hu, et al, 2021). Zhen et al predicted two important compounds (columbianadin and osthole) and two key targets (PTGS1 and PTGS2) by integrating UPLC–MS/MS and network pharmacology (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%